MODERNISASI KELEMBAGAAN PESANTREN DALAM PERSPEKTIF AZYUMARDI AZRA - Syafrawi, Syafrawi (Universitas Islam Madura, 2019)
Pesantren is an Islamic educational institution that has advantages both in terms of scientific traditions as well as the transmission and intensity of Muslims. The swift current of globalization has threatened the existence of pesantren, so that the idea of modernization has arisen in the environment of pesantren in order to answer the challenges of the need for social transformation. However, many people worry about the modernization of pesantren-oriented ideas which can now influence the identity and main functions of pesantren.